The effect of vegetable oils and animal fat supplement in a diet on the reproductive performance in sows - Paschma, Jolanta; Alaviuhkola, Timo; Suomi, Kaija (po, 1996)
It is found that supplementing the diets with rapeseed oil, soybean oil or tallow during late pregnancy and lactation had no clear beneficial effect on the number of piglets born alive, their growth during lactation or other reproductive characteristics of sows. Fat supplements increased fat content of colostrum and in most of the trials also milk fat content. Soybean oil and tallow were slightly better than rapeseed oil as fat supplements to the sows diets.
Lehti on ilmestynyt 1997
Keywords: Ko; emakot; sika; rehut; ruokinta; kasviöljyt